The options of different actor groups to address drivers of soil biodiversity change - Bartosz Bartkowski; Nico Eisenhauer; Frank Glante; Christina Lachmann; Jörg Römbke; Matthias Rillig; Christian Ristok; Anja Schmidt; Doreen Babin (Soil Organisms)
Soil biodiversity change is the consequence of a broad range of direct and indirect anthropogenic drivers. Understanding these drivers and the options to address them is essential for sustainability. However, evidence especially on indirect drivers of soil biodiversity change is scarce and limited. In this paper, we synthesize the available evidence with a focus on Germany to outline the roles played by three broad groups of actors – land users and land owners, policy makers and administration as well as consumers, citizens and civil society – in the context of soil biodiversity change. We use this evidence to propose options for action that are available to each group of actors. We conclude by arguing that, given the role of soil biodiversity as the invisible foundation of all terrestrial ecosystems and the associated complexity of the challenge, a concerted effort across actor groups is likely necessary to effectively address and protect soil biodiversity.